Preliminary list and visual guide of macrofungi of the Puyango Petrified Forest-Ecuador - Cruz, Darío; Masache, Débora (ACI Avances en Ciencias e Ingenierías, 2023)
Ecuador is a Megadiverse country in Flora, Fauna and Funga, as well as to unique ecosystems such as the Puyango Petrified Forest. This forest has not been investigated for its fungal diversity. In the present work, a preliminarily list and quick visual guide of mainly wood-decomposing macrofungi is recorded for the first time for the Puyango Petrified Forest. The results suggest a great diversity of fungi for this forest, where 28 observations correspond to 28 morphospecies. This information marks the baseline for future research projects to show and value the neotropical fungi diversity in this protected area declared National Heritage of Ecuador.
Keywords: El Oro; Loja; neotropical fungi; fungal diversity